Feline Wharton’s jelly-derived mesenchymal stem cells as a feeder layer for oocytes maturation and embryos culture in vitro - Baouche, Meriem; Ochota, Małgorzata; Mermillod, Pascal; Locatelli, Yann; Nizanski, Wojciech (Frontiers in Veterinary Science, 2023)
Introduction: Due to their capacity to release growth factors and cytokines, co-culture using mesenchymal stem cells has been considered a good alternative to promoting the maturation of the oocytes and the embryo's development quality in vitro in different mammalian species. In this regard, we investigated the effect of feline Wharton's jelly MSCs as feeders layer in oocyte maturation-consequently, the development of resulting embryos in co-culture.Methods: Oocytes with dark cytoplasm and a few layers of cumulus cells were collected and subjected to in vitro maturation and embryo culture using commercial media with and without MSCs addition. The oocytes' nuclear maturation and the degree of cumulus expansion in different groups were assessed after 24 hours; the development of the embryo was evaluated every 12 hours until day eight. Although MSCs increased the proportion of cumulus cells oocytes exhibiting cumulus expansion, there were no significant differences in the percentage of matured oocytes (Metaphase II) among the groups (P > 0.05). However, the embryo development differs significantly, with a higher cleavage, morula, and blastocyst percentage in oocytes matured with MSC co-culture conditions than in commercial media alone (p < 0.05). Also, we observed higher morula and blastocyst rates in the embryos co-cultured with MSCs during the in vitro culture (P > 0.05). Based on our results, the co-culture with MSCs during the oocyte maturation resulted in better embryo development, as well as the MSCs addition during embryo culture returned an increased number of morula and blastocysts. Further research is needed to fully understand and optimize the use of MSCs in oocyte maturation and embryo development.